Smart Catalogue Mobile Application (SCM) with Beacon Device - Odzaly, Edzreena Edza Binti; Harisi, Abdul Hakim Hanif; Kamala Azmi, Adlin Sofea; Mohd Nasir, Nurul Najihah; Bakari, Syaiful Fikri (2020)
Catalog is one way of promoting their business, goods and services to the customer by way of supermarket, shop and mart. The printed catalogue has been the helpful approach of promoting to the customers for the last decades. Unfortunately, there have been massive issues with such a printed catalogue. The purpose of Smart Catalogue Mobile Application (SCM) is to create a smart catalogue mobile application to the customer smartphone. This application is use Internet of Things product which is beacon device that will detect and send a push notification towards the customer smartphone when the customer enters the store. The SCM project will solve the problem that occurred on printed catalogue. Besides, SCM have many more advantages than printed catalogue which are SCM provide a push notification, SCM provide beacon notification and SCM developed for green development. For the testing of SCM catalogue, WW Food Mart has been chosen to be first store that used SCM catalogue.